Swiss ball gymnastics in the process of correcting musculoskeletal disabilities in students - Kiryanova, L.A.; Morozova, L.V.; Udalova, M.A. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to justify the developed programme for correcting musculoskeletal disabilities in students of special medical group A. Methods and structure of the study. To achieve this goal, the following methods were used: analysis of literary sources on the problem under study; pedagogical observations of the progress of educational and practical physical education classes at the university, a survey in the form of questionnaires, pedagogical testing, pedagogical experiment, mathematical and statistical data processing. The study involved 2nd-year full-time students of the special medical group of health A with the musculoskeletal system disabilities (n=32). Results and conclusions. The article discusses the results of the application of the physical rehabilitation program in the special medical health group A for disabilities of the musculoskeletal system, aimed at the use of swiss ball gymnastics, aimed at correcting physical abnormalities in the state of health of students.